The Impact Explorative Study of Teachers’ Perception on Online Learning Based on Technology Accepted Model - Rukminingsih, Rukminingsih; Novianti, Hartia; Bhatt, Kiritkumar; Rukmi, Nala Sita (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This study aims to offer teachers' perspectives on the effects of integrating online learning, utilizing technology accepted models (TAM) by Davis, during the spread of the Corona virus. This study employed an exploratory case study to dig up further about English teachers’ perception toward online learning based on TAM. The participants consisted of 20 SMPN teachers to respond the questioner and 5 SMPN teachers to answer the interview in Jombang region, East java, Indonesia. The data were obtained from questionnaires and interviews developed based on TAM. All participants completed online research questionnaires with Google Form application. And was followed by interviews to support the finding from questionnaire. The results indicated that participants held a favorable opinion about the perceived utility, convenience of use, and behavioral intention of online learning systems.   The majority of teachers agreed on online learning. Although the teachers faced multiple challenges when conducting online classes, they remained optimistic about utilizing technology for remote instruction.